PENGARUH PROMOSI KESEHATAN DENGAN MEDIA VIDEO TERHADAP PENINGKATAN PENGETAHUAN HEALTHY RELATIONSHIP SISWA-SISWI SMA "A" JAKARTA SELATAN TAHUN 2023 - Aliya Kinanti Prasetya (2024)
Reproductive health issues among adolescents, specifically concerning risky relationship behavior, are a pressing contemporary concern. This behavior often encourages premarital sexual activities and toxic relationships. To address this, a research study was conducted in 2023 focusing on Class XI students of SMA "A" South Jakarta. The study utilized a quantitative quasi-experimental design, employing a two-group pretest-posttest approach. The sample comprised 252 respondents selected through simple random sampling from all Class XI students of SMA "A" South Jakarta. The research aimed to assess knowledge and attitudes before and after health promotion through video media on healthy relationships. Students willingly participated, with dropouts excluded from the study. Data collected with pretest post-test questionnaire (Google Form) and analyzed with Wilcoxon. The results demonstrated a significant enhancement in both knowledge and attitudes among SMA "A" South Jakarta students regarding healthy relationships. The disparity in levels of understanding and attitudes before and after exposure to the educational video material was notable, with a p-value of 0.000 (p < 0.05). The findings suggest that sharing this educational video media is beneficial, and SMA "A" should consider continuing education through video media or other reliable sources for future generations.